Perancangan Sistem Infomasi Pendaftaran Pelayanan Administrasi Terpadu Berbasis Web di Kecamatan Buluspesantren - Janji Prasetya, Guyub; Sari, Fitriani Dwi Ratna; Fatich, El Vionna Laellyn Nurul (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2023)
Buluspesantren sub-district is a public service provider, namely administrative services in an integrated sub-district manner. The types of services provided are family cards, birth certificates, child identity cards, electronic identity cards, migration, migration, death certificates, provision of recommendations, and general legalization. Of the many types of services required system design to facilitate the process of registration and reporting. The resulting system will later be developed using the waterfall method, the PHP programming language, and the MySQL database.